Management of prison education model - Lopez, Emma Lina F. (2006)
The study aimed to fill in the research gap relative to how education can provide the coping mechanism for inmates while incarcerated and upon their release. The McKinsey's Seven-S approach was used as the framework in analyzing the current situation of prison education at the NBP. The framework made possible the formulation of a management approach to prison education and answers the four questions posed in coming up with an intrinsic Filipino research-based model. From the research, a new model which covers the offender' transition from being an ex-offender to being an income-generating employee, was devised. From the correctional institution, assistance is made available in their search for jobs or other income-generating ventures. Thus, they are helped in mainstreaming again with civilians in the community.
Thesis (Ph.D. Educational Administration)--University of the Philippines, Diliman.
Keywords: Prisoners -- Education -- Philippines; Prison administration -- Philippines